Survey of Expression of Aflatoxin Production Regulator Gene (aflR) in Aspergillus Parasiticus by Alpinia Galanga L and Dorema Aucheri - Arab-Mazar, Zahra; lotfali, Ensieh; Ghadjari, Ali; Aghaei Gharehbolagh, Sanaz; Mohammadi, Reza; Nouripour-Sisakht, Sadegh (Novelty in Biomedicine, 2018)
Background: Aflatoxins are one of the highly toxic secondary metabolites, which are mainly produced by Aspergillus parasiticus. This species frequently cause of food and agricultural products contamination including cereals, peanuts, and crops in the field. During recent years, researchers have considered research on elimination of aflatoxin and antifungal effects of medicinal herbals, such as Alpinia galanga L and Dorema aucheri. In this study, the effect of A.galanga L and D.aucheri a natural compound was examined on Aspergillus parasiticus growth, aflatoxins production and the aflR gene expression. Materials and Methods: Antifungal susceptibility A.galanga L and D.aucheri was performed according to CLSI document M38-A2. Quantitative changes in aflR gene level of expression were analyzed by Real-time PCR method. Results: Our result obtained that the MIC of extracts on A. parasiticus growth 250 mg/mL for D.aucheri and 800 mg/mL for A.galanga L. D.aucheri has antitoxic properties as well as its effective ability to decrease aflatoxin production. The level of aflR gene expression was decreased significantly after the exposure of fungal cell to D.aucheri extract, but A.galanga L didn’t have significant effect. Conclusion: This research indicated that D.aucheri has antifungal effects more than A.galanga L. Due to our obtained result we can suggest that D.aucheri herbal extract may have antifungal potential in medicine or agriculture.